IMPROVING CRITICAL THINKING SKILLS THROUGH INNOVATIVE LEARNING AT SDN 45 BANDA ACEH - Ainal Mardhiah; Siti Mayang Sari; Muhammad Zulhairi Bin Zubairi (Sensei International Journal of Education and Linguistic, 2024)
Education has an important role in shaping individual character, knowledge and skills, especially in the era of globalization and the industrial revolution. Critical thinking skills are essential in dealing with complex problems, making decisions, and contributing to the development of society. In the educational context, improving critical thinking skills is the main goal, considering the rapid changes in the social, economic and technological landscape. Innovative learning is the key to achieving this goal, considering the diversity of each individual's learning methods. The aim of this research is to determine the improvement of critical thinking skills through innovative learning at SDN 45 Banda Aceh. This research uses a qualitative approach with descriptive research type. Interview results show that the implementation of a project-based approach and the use of technology has increased student interest and participation. The teacher's role as a facilitator of a supportive learning environment is key in achieving positive results. Good student response and parental support reinforce the value of innovative learning. Despite facing infrastructure and teacher training challenges, ongoing efforts are being made to overcome these obstacles.